2021
DOI: 10.1016/j.ebiom.2021.103536
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and senescence markers indicate an accelerated ageing-like state in women with preeclamptic pregnancies

Abstract: Background: Preeclampsia is a pregnancy-specific hypertensive disorder characterized by proteinuria and/or multisystem involvement. Disease-specific therapy has yet to be developed due to the lack of understanding of underlying mechanism(s). We postulate that accelerated ageing in general, and particularly cellular senescence, play a role in its pathophysiology. Methods: We compared women with preeclampsia vs. normotensive pregnancies with respect to epigenetic markers of ageing and markers of senescence in ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…It has been postulated that accelerated cellular senescence may represent one mechanism of accelerated cardiovascular aging in women with HDPs. 80,81 There appears to be a strong genetic contribution to preeclampsia risk. Women whose first-degree relatives had preeclampsia have a 2-to 3.5-fold risk of developing preeclampsia.…”
Section: Association Of Hdps With Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that accelerated cellular senescence may represent one mechanism of accelerated cardiovascular aging in women with HDPs. 80,81 There appears to be a strong genetic contribution to preeclampsia risk. Women whose first-degree relatives had preeclampsia have a 2-to 3.5-fold risk of developing preeclampsia.…”
Section: Association Of Hdps With Cvdmentioning
confidence: 99%
“…It has been postulated that accelerated cellular senescence may represent one mechanism of accelerated cardiovascular aging in women with HDPs. 80,81…”
Section: Pregnancymentioning
confidence: 99%
“…We will dissect such potential mechanisms in future studies. Additional future studies are needed to: (1) ascertain if CSF α-Klotho increases after administering senolytics to humans with Alzheimer's disease (currently being studied in the clinical trials, NCT04785300 and NCT04685590), (2) compare blood indices of senescent cell burden to urinary α-Klotho in patients across the age spectrum in other current and future clinical studies of senolytics, and (3) ascertain why in pre-eclampsia, a condition that we found is associated with increased senescent cells 86 and that has been linked to decreased urinary α-Klotho, 87 plasma α-Klotho is increased. 88 This discrepancy between α-Klotho in urine and plasma in pre-eclampsia is consistent with the previous finding that in chronic kidney disease (CKD), plasma α-Klotho is not related to kidney function and does not predict adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, senescent cells are characterized by abnormal paracrine secreting mixture of cytokines, chemokines, and matrix metalloproteins to influence the neighboring cells and microenvironment [ 14 ]. Although there exists the physiological senescence in the placenta as pregnancy advances to term [ 15 ], the preeclamptic placentas showed accelerated senescence [ 16 18 ]. Thereinto, preeclamptic PMSCs showed abnormal proliferation [ 19 ], arrested cell cycle [ 8 ], overexpressed p16, overactivated SA- β -gal, and abnormal secretory phenotype [ 11 ].…”
Section: Introductionmentioning
confidence: 99%